Impact of dealing with bereaved clients on the psychological wellbeing of veterinarians. Issue 10 (31st July 2019) - Dow, MQ; Chur‐Hansen, A; Hamood, W; Edwards, S
Abstract : Background: Research has identified that members of the veterinary profession are at high risk of occupational stress, burnout, poor psychological wellbeing and an elevated rate of suicide. Although scholarly interest in veterinarians has increased in recent years, relatively few studies have specifically examined the emotional work in veterinary interactions and what effect dealing with companion animal owners' grief has on the wellbeing of veterinarians. The purpose of this study was to determine if dealing with bereaved clients affected the psychological wellbeing of veterinarians. The concept of compassion fatigue was explored, including whether veterinarians believed that their training had equipped them for communicating with grieving clients. Methods: Veterinary surgeons registered in South Australia in 2015 were invited to complete an online survey, with 105 participants responding. Results: Many participants, particularly female and younger veterinarians, were experiencing mild to severe psychological distress and nearly half of the sample was experiencing high to very high levels of compassion fatigue. No participants reported seeking psychological or other professional mental health support and the majority had not referred a grieving client to a psychologist or other mental health professional. A significant proportion of veterinarians felt their own mental health was affected by dealing with clients grieving the loss of a companion animal. Discussion: The findings are discussed in terms of increasing the wellbeing of veterinarians through improved curriculum training and workplace health promotion, particularly considering the high suicide rate reported for the profession.